An Analysis of Maxim Flouting in Male and Female Roleplay AI Chatbot Responses - Walewangko, Khenisa Elisyeva; Halim, Suwarni Wijaya (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
Conversational implicature is a tool often used in everyday speech by both male and female alike. It gives the speaker a way to say something without directly mentioning the idea. There is a general assumption that males and females communicate differently from just the basis of each gender. This study in particular investigates this claim to see if the same assumption will be aligned with the result found when it comes to the topic of maxim flouting. The data collected in this study are from the responses of AI roleplay chatbots from the website Character AI in which the bots are supposed to mimic interactions between humans. By selecting a character named Blackwall for the male and Shadowheart for the female, the researchers chatted and roleplayed with both bots. It was found that the two bots produced utterances that flouted the four maxims, i.e., the maxim of quantity, quality, relation, and manner. The study found that the male flouted a total of 19 maxims, while the female only flouted the maxims 8 times within the 200 replies of each bot. The male chatbot flouted maxim of quality nine times, maxim of relation five times, maxim of manner three times, and maxim of quantity twice. Meanwhile, the female chatbot flouted the maxim of quality seven times and maxim of relation once.  The results revealed that the male chatbot flouted more than the femalebot did, but both flouted the maxim of quality the most. In addition, the differences in the data shows that the malebot preferred to use rhetorical questions which differs with the female chatbot which used metaphor more.